The Bone Sparing Effects of 2-Methoxyestradiol Are Mediated via Estrogen Receptor-α in Male Mice - Eriksson, Anna L. (Endocrinology, 2016)
2-Methoxyestradiol (2ME2), a metabolite of 17β-estradiol (E2), exerts bone sparing effects in animal models. We hypothesized that the underlying mechanism is back conversion of 2ME2 to E2, which subsequently acts via estrogen receptor (ER)α. We measured serum E2 levels in orchidectomized wild-type (WT) mice treated with 2ME2 66.6 μg/d or placebo. In placebo-treated animals, E2 was below the detection limit. In 2ME2-treated mice, the serum E2 level was 4.97 ± 0.68 pg/mL. This corresponds to the level found in diesterus in cycling female mice. Next, we investigated bone parameters in orchidectomized WT and ERα knockout mice treated with 2ME2 or placebo for 35 days. 2ME2 (6.66 μg/d) preserved trabecular and cortical bone in WT mice. Trabecular volumetric-bone mineral density was 64 ± 20%, and trabecular bone volume/total volume was 60 ± 20% higher in the metaphyseal region of the femur in the 2ME2 group, compared with placebo (P < .01). Both trabecular number and trabecular thickness were increased (P < .01). Cortical bone mineral content in the diaphyseal region of the femur was 31 ± 3% higher in the 2ME2 group, compared with placebo (P < .001). This was due to larger cortical area (P < .001). Three-point bending showed an increased bone strength in WT 2ME2-treated animals compared with placebo (maximum load [Fmax] +19±5% in the 2ME2 group, P < .05). Importantly, no bone parameter was affected by 2ME2 treatment in ERα knockout mice. In conclusion, 2ME2 treatment of orchidectomized mice results in increased serum E2. ERα mediates the bone sparing effects of 2ME2. The likely mediator of this effect is E2 resulting from back conversion of 2ME2.